Chronobiology, sleep-related risk factors and light therapy in perinatal depression: the "Life-ON" project. Issue 1 (December 2016) - Baiardi, Simone; Cirignotta, Fabio; Cicolin, Alessandro; Garbazza, Corrado; D'Agostino, Armando; Gambini, Orsola; Giordano, Alessandra; Canevini, Mariapaola; Zambrelli, Elena; Marconi, Anna; Mondini, Susanna; Borgwardt, Stefan; et al.
Abstract Background Perinatal depression (PND) has an overall estimated prevalence of roughly 12 %. Untreated PND has significant negative consequences not only on the health of the mothers, but also on the physical, emotional and cognitive development of their children. No certain risk factors are known to predict PND and no completely safe drug treatments are available during pregnancy and breastfeeding. Sleep and depression are strongly related to each other because of a solid reciprocal causal relationship. Bright light therapy (BLT) is a well-tested and safe treatment, effective in both depression and circadian/sleep disorders. Methods In a 3-year longitudinal, observational, multicentre study, about 500 women will be recruited and followed-up from early pregnancy (10–15 gestational week) until 12 months after delivery. The primary aim of the present study is to systematically explore and characterize risk factors for PND by prospective sleep assessment (using wrist actigraphy, polysomnography and various sleep questionnaires) and bloodbased analysis of potential markers during the perinatal period (Life-ON study). Secondary aims are to explore the relationship between specific genetic polymorphisms and PND (substudy Life-ON1), to investigate the effectiveness of BLT in treating PND (substudy Life-ON2) and to test whether a short term trial of BLT during pregnancy can prevent PND (substudy Life-ON3). Discussion The characterization of specific predictive and risk factors for PND may substantially contribute to improve preventive medical and social strategies for the affected women. The study results are expected to promote a better understanding of the relationship between sleep disorders and the development of PND and to confirm, in a large sample of women, the safety and efficacy of BLT both in prevention and treatment of PND. Trial registration ClinicalTrials.govNCT02664467 . Registered 13 January 2016.